2018
DOI: 10.15270/54-1-611
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Review of Resilience Theory and Its Relevance for Social Work

Abstract: A CRITICAL REVIEW OF RESILIENCE THEORY AND ITS RELEVANCE FOR SOCIAL WORK Adrian D van BredaAs resilience theory gains traction as a theoretical framework for research in social work, it is important to engage with it critically. This article provides a critical review of resilience theory, drawing on an array of key authors, dating back fifty years. The review addresses three aspects of resilience theory: its definition, the construction of adversity and outcomes, and the nature and scope of resilience process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
253
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(268 citation statements)
references
References 54 publications
9
253
1
5
Order By: Relevance
“…Many students spoke of the support of family and consequently this support bolstered their resilience. Community resilience explored by Van Breda (2001) refers to the family as a protective factor increasing the resilience of individuals. For some students, colleagues and friends helped put low grades into perspective.…”
Section: Coping With Study On a Level 1 Modulementioning
confidence: 99%
“…Many students spoke of the support of family and consequently this support bolstered their resilience. Community resilience explored by Van Breda (2001) refers to the family as a protective factor increasing the resilience of individuals. For some students, colleagues and friends helped put low grades into perspective.…”
Section: Coping With Study On a Level 1 Modulementioning
confidence: 99%
“…SLA also shares conceptual synergy with other theories such as resilience, asset-based community development and the strengths perspective in that the focus is on mutual trust, norms and community networks, which are perceived as key features of social life that facilitate or ease social interactions encouraging people to work together towards shared goals ((Van Breda, 2018;Wissing & van Eeden, 2002). This framework implies that single-mother households should be able to mobilise their members to reduce the risk of dysfunction and support optimal adaptation.…”
Section: Relevance Of the Sustainable Livelihood Approachmentioning
confidence: 99%
“…Resilience is a multidimensional construct that varies with context, culture and time [10,11]. Despite that the operationalization of this construct has considerably varied within the literature [12], various empirical ndings and models have described resilience as having three important components: successful adjustment to stress, the propensity to experience positive emotions in the face of stressful situations, and optimism [13,14]. It is suggested that cognitive interpretations of individuals about a stressful situation and the way they cope with adverse circumstances seem to be associated with their resilience in the face of distressing events [13,14].…”
Section: Introductionmentioning
confidence: 99%